2016
DOI: 10.1016/j.jpsychires.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Transferring the blues: Depression-associated gut microbiota induces neurobehavioural changes in the rat

Abstract: The gut microbiota interacts with the host via neuroimmune, neuroendocrine and neural pathways. These pathways are components of the brain-gut-microbiota axis and preclinical evidence suggests that the microbiota can recruit this bidirectional communication system to modulate brain development, function and behaviour. The pathophysiology of depression involves neuroimmune-neuroendocrine dysregulation. However, the extent to which changes in gut microbiota composition and function mediate the dysregulation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
939
9
28

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 1,302 publications
(1,017 citation statements)
references
References 60 publications
41
939
9
28
Order By: Relevance
“…The antibiotic cocktail was administered in drinking water to avoid any adverse effects from chronic stress induced by alternative administration methods such as oral gavage. The antibiotic cocktail consisted of ampicillin (1g/L), vancomycin (500mg/L), and ciprofloxacin HCL (20mg/L), imipenem (250mg/L) and metronidazole (1g/L) and was chosen based on published protocols from our group (Kelly et al, 2016) and others (Heimesaat et al, 2013) and was made up in autoclaved 5 water and changed every 3 days. Control animals received autoclaved water without any antibiotics which was also changed every 3 days.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…The antibiotic cocktail was administered in drinking water to avoid any adverse effects from chronic stress induced by alternative administration methods such as oral gavage. The antibiotic cocktail consisted of ampicillin (1g/L), vancomycin (500mg/L), and ciprofloxacin HCL (20mg/L), imipenem (250mg/L) and metronidazole (1g/L) and was chosen based on published protocols from our group (Kelly et al, 2016) and others (Heimesaat et al, 2013) and was made up in autoclaved 5 water and changed every 3 days. Control animals received autoclaved water without any antibiotics which was also changed every 3 days.…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…They demonstrated that a fecal transfer of microbiota from patients diagnosed with major depressive disorder (MDD) to germ-free mice, resulted in more depression-like behaviors for these mice as compared to germ-free mice that were colonized with healthy individuals' microbiota. Kelly et al [32] found the same effect of a fecal transfer from MDD patients to an antibiotics-induced microbiotadepleted rat model. While they failed to observe any significant differences in hippocampal BDNF expression associated with the depression, rats who received the depressive gut microbiota had an increased kynurenine/tryptophan ratio in blood.…”
Section: Introductionmentioning
confidence: 75%
“…Recently, several studies have demonstrated altered gut microbiota composition in depression (Jiang et al, 2015;Kelly et al, 2016a;Naseribafrouei et al, 2014) and suggest that this altered gut microbiota composition may play a causal role in the development of certain features of depression (Kelly et al, 2016a;Zheng et al, 2016), though the precise mechanisms have yet to be elucidated. To date, only one small study has investigated a probiotic intervention in depressed patients (Akkasheh et al, 2016).…”
Section: Discussionmentioning
confidence: 99%